Sentença trabalhista de dano moral: análise do plano de texto, do ponto de vista e da responsabilidade enunciativa - Medeiros, Júlia Ohana Alves (2023)
Analyzing the discursive genre labor sentence of moral damage, circumscribed to the legal domain, regarding the phenomena of text plan, point of view and enunciative responsibility is our purpose in this work. Therefore, we aim to identify, describe, analyze and interpret a) how the text plan of the analyzed sentences is constituted; b) the points of view articulated in the decision; and c) the linguistic markers related to the enunciative responsibility of the first speaker/enunciator (S1/E1). In this way, we executed a research with a qualitative approach, fundamentally interpretative, and with documentary analysis through the inductive method. The corpus consists of thirteen labor sentences, one from each Labor Court of Natal, RN (Brazil), linked to the Tribunal Regional do Trabalho/Regional Labor Court of the 21st Region (TRT21), responsible for promoting justice in labor relations in the state of Rio Grande do Norte (RN). We selected the sentences considering the following criteria: 1) that the sentence is a definitive one; 2) that it follows the common procedural rite; 3) that it addresses a claim for moral damages; and 4) that it has been judged between 2018 and 2020, considering that the last Labor Court of Natal, was created in September 2017. From this last Court, we have sentences with the established criteria as of 2018. The delimitation of the final period is the year immediately prior to our entry into the master's program. For data collection, we resorted to the website www.trt21.jus.br, which is publicly accessible. The research is based on the theoretical postulates of Textual Analysis of Discourses, Theory of Enunciation and Discourse Analysis. In this direction, we follow authors who work with Enunciative Responsibility, among them, Adam (2011), Rabatel (2017), Rodrigues (2016, 2017) and Passeggi et al. (2010), in dialogue with linguistic approaches related to the Point of View, from the perspective of Rabatel (2013, 2016), and to the Text Plan, with Adam (2011, 2021, 2022), Rodrigues and Marquesi (2021), Marquesi (2016 ), Cabral (2013), Marquesi, Cabral and Rodrigues (2020) among others. Data analysis points to the following results: we found that the text plan of the analyzed sentences is presented as fixed or conventional, but with variations resulting from the organization of each magistrate. We observed the predominance of non-assumption of enunciative responsibility in the report section, which was evident by the use of impersonality markers and indirect speech by the S1/E1. We also identified that, although there is no assumption of enunciative responsibility in the reasoning of the sentences, which is evident by the use of indirect and direct speeches by the judge, it is predominant, in this textual zone, the assumption of enunciative responsibility by the magistrate, as a S1/E1, what was possible to verify, mainly, by spatial deictic markers, modalities and verbs in the first person singular. In the device section, we found that the assumption of enunciative responsibility predominates, even though the judge is implicitly engaged with the propositional content conveyed. As for the point of view, we found that the linguistic markers point to the argumentative orientation of the judge, sometimes in the sense of condemning the defendant to pay compensation for moral damages and sometimes in the sense of rejecting the claim of the plaintiff, predominating in the sentence the point of view narrated and represented in the report and asserted in the reasoning and device sections.